Pathological Findings in the Adrenal Glands of 80 Dogs - da Silva, Elisângela Olegário; Di Santis, Giovana Wingeter; Headley, Selwyn Arlington; Loureiro Bracarense, Ana Paula Frederico Rodrigues (Acta Scientiae Veterinariae, 2018)
Background: The adrenal glands development important endocrine functions and can be affected by primary or secondary diseases. These adrenal gland pathologies may induce clinical syndromes resulting from abnormalities in the production and secretion of hormones. Data about pathological changes in dogs are scarce. Therefore, the aim of the present study was to identify and evaluate the histopathological and epidemiological features of adrenal changes in dogs submitted to necropsy examination from 2005 to 2016 in a Veterinary Teaching Hospital, Londrina, Paraná, Brazil. Material, Methods & Results: During this period, 80 animals presented alterations of adrenal gland, representing 5.5% of all necropsied dogs. The pure breed dogs representing 58.6% and mixed breed 41.4%; 53.4% were female and 46.6% were male. The non-neoplastic adrenal lesions were more frequently (57.5%) compared to the neoplastic changes (42.5%). Most of the adrenal glands lesions occurred in older dogs (60%), following by the middle aged (31.25%) and young dogs (8.75%). The main non-neoplastic lesions observed in the adrenal glands were of hyperplastic (69.5%) and circulatory (26%) origin, among the earlier, 68.8% were diffuse hyperplasia and 31.2% nodular hyperplasia. The nodular hyperplasia was classified as micronodular multifocal in 40% of the glands with nodular hyperplasia, macronodular multifocal in 30%, micronodular diffuse in 20%, and micronodular focal in 10%. The neoplasms observed were adrenocortical adenoma (ACA) in 44.1%, pheochromocytomas in 23.5% and adrenocortical carcinomas (ACC) in 11.7% of the dogs with adrenal tumors. Metastasis from other primary tumors were observed in 20.6%. Discussion: The data in veterinary literature about the frequency of changes in adrenal gland of dogs are scarce and focus features of diagnosis by ultrasound examination. Most of the adrenal changes observed in the present study were incidental findings observed during the necropsy examination and no specific clinical signs were observed. Non-neoplastic adrenal lesions, mainly of hyperplastic origin, were more frequently observed compared to the neoplastic changes. Differing from previous studies, the diffuse hyperplasia was the most common non neoplastic finding in the adrenal glands. Considering the subclassification of nodular hyperplasia, the multifocal micronodular and macronodular multifocal pattern were the most frequent. In veterinary literature, there are no data about frequency of nodular hyperplastic subtypes. However, in humans the subclassification of nodular hyperplasia is associated to development of endocrine disorders. Previous studies reported lower incidence of neoplastic changes in adrenal gland of dogs compared to the present results. The adrenocortical adenoma was the most common primary tumor, followed by the adrenocortical carcinoma, pheochromocytoma and adrenocortical carcinoma. Congestion and hemorrhage were common findings observed in the adrenal gland primary tumors. On the other hand, necrosis and inflammatory infiltrate were observed only in the adrenocortical carcinomas. These histopathological features may be used as tool in the differential diagnosis between well differentiated adrenocortical carcinoma and adenoma. The histopathological examination was fundamental to differential and definitive diagnosis of all canine adrenal gland disorders observed.